(untitled) (Islas, 2023)
Introduction: This brief and preliminary study is dedicated to describing and commenting on the bibliographic information provided by Esteban Rodríguez Herrera and specifying its use as sources to illustrate the uses of the terms collected in his lexical repertoire. This practice of exemplifying entries was innovative at the time. Methods: A descriptive method was employed to reveal the peculiarities of the bibliography used by the prominent lexicographer and its use in citations of authorities. Results: As this work represents an initial approach to the bibliographic sources of the Léxico Mayor de Cuba, only some ideas are advanced based on the analysis of a sample. Conclusions: The abundance and diversity of sources consulted by the author are confirmed, as well as their relationship with the lexicographic practice of using citations from authorities, most of which are declared in the bibliography.